Organizational commitment and case study on the Union of Municipalities of Marmara - (:unkn) unknown (My University, 2010)
The present paper, written on the subject of institutional commitment, presents a theoretical and empirical study aiming at measuring the level of institutional commitment of the staff of the Union of Municipalities of Marmara. The field study realised for the purpose of the paper measured levels of affective, continuance and normative commitments of the workers. In addition, the correlation between the personal and demographic characteristics of the staff members and the types of their institutional commitment have been analyzed. Thus, it has been established that the workers are strongly committed to the organization by affective and normative commitment, while continuance commitment is less relevant. The relationship between this finding and the personal and demographic characteristics have been determined in details. The study concludes that the management of the union shall take measures to strengthen the continuance commitment. In this respect, some proposals have been elaborated. On the other side, some advices addressed to academicians who will realize studies on this subject have been listed.
Keywords: Municipality; Organizational commitment; Union